2013
DOI: 10.1364/oe.21.000172
|View full text |Cite
|
Sign up to set email alerts
|

A plasmon ruler based on nanoscale photothermal effect

Abstract: The determination of nanoscale distances or distance changes necessitates a nanoscale ruler. In the present paper, distance dependence of particle temperature in an optically heated gold nanoparticle pair is quantitatively investigated to explore the possibility of creating a plasmon ruler based on this effect. The two origins of the distance-dependence, i.e., electromagnetic coupling and thermal accumulative effect, are studied. For the particle temperature, a scaling behavior is found, and it suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 33 publications
5
43
0
2
Order By: Relevance
“…This concept was demonstrated theoretically by Qiu and coworkers, who showed that the LSPR peak positionc ould be tuned to 620 nm by decreasing the gap distance from 100 nm all the way down to 2nm ( Figure 10 A). [31] It is importantt o note that this effect is only prominentw hen the light polarization direction is parallel to the long axis of the dimer,w here ac lear red-shift in the LSPR is observed. If thep olarization direction is perpendicular to the long axis of the dimer,t he redshifted hybrid peak will not be observed.…”
Section: Plasmonic Hybridizationmentioning
confidence: 97%
“…This concept was demonstrated theoretically by Qiu and coworkers, who showed that the LSPR peak positionc ould be tuned to 620 nm by decreasing the gap distance from 100 nm all the way down to 2nm ( Figure 10 A). [31] It is importantt o note that this effect is only prominentw hen the light polarization direction is parallel to the long axis of the dimer,w here ac lear red-shift in the LSPR is observed. If thep olarization direction is perpendicular to the long axis of the dimer,t he redshifted hybrid peak will not be observed.…”
Section: Plasmonic Hybridizationmentioning
confidence: 97%
“…In 2012, Chen et al [82] studied photothermal effects in gold nanospheres finding structures entering a pre-melting regime at 519 K and changing sensitively shape around 795 K, much lower than bulk gold melting point (1337 K). Photothermal interaction between nanospheres has also been proposed as a plasmon ruler by Zhang et al in [83]; the effect is based on the sensitivity of the absorption power on the distance between two NPs placed on a substrate. Being able to measure the absorption differences, can lead to nanometric gaps characterizations.…”
Section: Heating Processes In Plasmonic Nanostructuresmentioning
confidence: 99%
“…Changing diameter of gold nanoparticles is a simple way to vary plasmon frequency. However, this way only changes plasmon frequency up to certain frequency [6]. Fabricating multishell of metallic nanoparticles is one effective way to produce two plasmon frequencies [7].…”
Section: Introductionmentioning
confidence: 99%